2001
DOI: 10.1016/s0960-8524(00)00167-x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of by-products from the tequila industry. Part 2: potential value of Agave tequilana Weber azul leaves

Abstract: The leaves ofthe agave plant are left in the field after harvesting the heads for tequila production. Different types ofagave leaves were isolated, classified, and their content in the total plant determined. The usable fractions were collected and their properties determined. Of the total wet weight of the agave plant, 54% corresponds to the agave head, 32% corresponds to materials which could be usable for sugar and fiber production which leaves 14% ofthe wet plant without apparent utility. The fractions wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 2 publications
4
65
0
6
Order By: Relevance
“…Thus, some degree of similarity can be observed in total lignin content between the obtained value (20.69 %) and that previously (21.1 %) reported by Kestur et al (2013); however, the total lignin content is higher than the values for raw fi ber (16.8 %) and cooked fi ber (7.2 %) reported by Iñiguez-Covarrubias et al (2001b) and reported by Iñi-guez et al (2005), respectively. In relation to the α-cellulose content, the value obtained (55.03 %) is higher than that reported (49.43 %) by Kestur et al (2013) and also higher than that reported (41.90 %) by Iñiguez et al (2005) but is lower than that reported (64.9 %) when raw material was used (Iñiguez-Covarrubias et al, 2001a).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Thus, some degree of similarity can be observed in total lignin content between the obtained value (20.69 %) and that previously (21.1 %) reported by Kestur et al (2013); however, the total lignin content is higher than the values for raw fi ber (16.8 %) and cooked fi ber (7.2 %) reported by Iñiguez-Covarrubias et al (2001b) and reported by Iñi-guez et al (2005), respectively. In relation to the α-cellulose content, the value obtained (55.03 %) is higher than that reported (49.43 %) by Kestur et al (2013) and also higher than that reported (41.90 %) by Iñiguez et al (2005) but is lower than that reported (64.9 %) when raw material was used (Iñiguez-Covarrubias et al, 2001a).…”
Section: Resultssupporting
confidence: 83%
“…Although studies on Agave an- gustifolia are scarce (Vera Guzmán et al, 2009;Esqueda et al, 2011;Mejía-Franco and Arzate-Fernández, 2011;Bautista and Smit, 2012; Martinez Gutierrez et al, 2012;Cruz-García et al, 2013;Allsopp et al, 2013), the potential benefi ts of this lignocellulosic material cannot be ignored. Additional research on its properties is needed so that future alternative uses may be identifi ed and contribute to economic activity by increasing development opportunities, as has occurred with other species (Iñiguez-Covarrubias et al, 2001a;Iñiguez-Covarrubias et al, 2001b;Piven et al, 2001;Gil-Vega et al, 2006;Bessadok et al, 2008; Velazquez-Jimenez et al, 2013). Cooked Agave angustifolia bagasse is a material with numerous fi bers and is a largely underutilized waste material from the mezcal (alcoholic beverage) industry; however, these fi bers, similar to other plant fi bers, are lignocellulosic materials with technical, economic and ecological potential and therefore could be used in different industries.…”
Section: Introductionmentioning
confidence: 99%
“…ºBrix and pH were also significantly higher in the older agave head (P < 0.05). The weights and diameters of both agave heads were lower than those reported by Arrizon et al (2010) for an agave head of 6.5 years; however, a similar weight was reported by Iñiguez-Covarrubias et al (2001) for an average of 30 agave heads of 7-9 years. In agreement with the present findings, Pinal et al (2009) reported higher ºBrix levels in musts from 8-year-old agaves than in those from 4-year-old agaves.…”
Section: Physicochemical Characterization Of Agave Tequilana Plants Osupporting
confidence: 52%
“…Tabla 1. Características y propiedades de la fibra de agave Iñiguez et al (2001), Bledzki et al (2004).…”
Section: Materiales Y Metodos Materialesunclassified
“…Dentro de ese tipo de fibras naturales, la fibra de agave de desecho del proceso de fabricación del tequila, además de ser una materia prima de costo ínfimo, posee elevada rigidez y resistencia específica, Iñiguez et al (2001), Bledzki et al 2004. Sin embargo, al igual que otras fibras de este tipo, es un material complejo, que al igual que la madera contiene esencialmente celulosa, hemicelulosa, lignina y extractivos según Ashori y Nourbakhsh (2010).…”
Section: Introductionunclassified